2020
DOI: 10.1007/s40430-020-02481-5
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic vibration-assisted turning of Titanium alloy Ti–6Al–4V: numerical and experimental investigations

Abstract: The machining of Titanium alloy, Ti-6Al-4V has got an extensive attention from industries like aerospace, medical, and biomedical plants due its unique properties like high strength at elevated temperature and better strength to weight ratio. Still, properties like reduced thermal conductivity, affinity to react with the tool and work hardening make difficult to cut it by conventional turning process. Ultrasonic vibration-assisted turning (UVAT) is one of the advanced turning method in which tool is allowed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The EN8 carbon steel was used as the booster material and it was fabricated in a cylindrical shape. The length of the cylindrical booster was calculated as [30] ( )…”
Section: Experimental Setup Of Uvat Processmentioning
confidence: 99%
“…The EN8 carbon steel was used as the booster material and it was fabricated in a cylindrical shape. The length of the cylindrical booster was calculated as [30] ( )…”
Section: Experimental Setup Of Uvat Processmentioning
confidence: 99%
“…In addition, regular ultrasonic vibration creates uniform and flat chips, which lowers the degree of deformation of the material [5]. Previous studies have shown that ultrasonic vibration cutting methods perform better at low cutting speeds [6,7]. This study applies ultrasonic vibration cutting to mechanically process polycrystalline zinc sulfide material, observing changes in surface characteristics with varying cutting speeds and analyzing the springback issue observed in conventional machining.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to continuous turning, the tool life improved multifold due to the discontinuous cutting nature. 2 Kandi et al 3 examined the effect of the input variables on the surface finish and tool wear in the UAT and CT of Ti6Al4V alloy. The authors reported that the surface finish obtained in ultrasonic vibration-assisted turning (UVAT) was much lower than CT.…”
Section: Introductionmentioning
confidence: 99%